2020
DOI: 10.1002/jsfa.10992
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of Pickering emulsion gels stabilized by zein/pullulan complex colloidal particles

Abstract: BACKGROUND Zein particles are unsuitable as stabilizers of Pickering emulsions because of their high hydrophobicity. However, few studies have reported on the use of a strong hydrophilic neutral polysaccharide to regulate its wettability. In this work, zein/pullulan complex particles (ZPPs) were formulated by an anti‐solvent method to fabricate Pickering emulsions. RESULTS The presence of pullulan increased the size, decreased the zeta, and provided excellent resistance to the gravitational separation of zein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 66 publications
4
13
0
Order By: Relevance
“…This result indicated that the emulsion structure loading with PMFs was destroyed during shearing, which weakened the interaction between the oil droplets. 28 This phenomenon was consistent with our previously reported result, 17 and an analogous observation was also confirmed by Dammak et al, 29 which reported that the apparent viscosity of all Pickering emulsions loading with hesperidin gradually decreased with the increase of shear rate. For all Pickering emulsions, the storage modulus (G 0 ) was substantially higher than the loss modulus (G 00 ) within 0.1-10 Hz (Fig.…”
Section: Rheological Propertiessupporting
confidence: 92%
See 3 more Smart Citations
“…This result indicated that the emulsion structure loading with PMFs was destroyed during shearing, which weakened the interaction between the oil droplets. 28 This phenomenon was consistent with our previously reported result, 17 and an analogous observation was also confirmed by Dammak et al, 29 which reported that the apparent viscosity of all Pickering emulsions loading with hesperidin gradually decreased with the increase of shear rate. For all Pickering emulsions, the storage modulus (G 0 ) was substantially higher than the loss modulus (G 00 ) within 0.1-10 Hz (Fig.…”
Section: Rheological Propertiessupporting
confidence: 92%
“…In our previous study, ZPPs were formulated by anti-solvent method as a new stabilizer for Pickering emulsions. 17 ZPPs was close to neutral wettability when the zein-to-pullulan ratio was 15:1, which is conducive to the preparation of stable emulsion. The results exhibited that the Pickering emulsion has long-term stability against coalescence and Ostwald ripening.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The Pickering particles stabilized emulsion gels enhanced the bioaccessibility of the impregnated curcumin by 22.2%, indicating gels as an effective delivery system for lipophilic bioactive substances. ( 74 ) fabricated Pickering emulsion gels by encapsulating medium chain triglyceride oil (50-60%) stabilized by complex colloidal particles (zein-pullulan - 2 wt%). The resultant gels showed excellent stability against coalescence and phase separation and no oil leakage was noticed even after 30-days of storage at room temperature.…”
Section: Mixed Emulsion Gelsmentioning
confidence: 99%